Polycomb protein eed is required for neurogenesis and cortical injury activation in the subventricular zone - Sun, B; Chang, E; Gerhartl, A; Szele, F (Oxford University Press, 2018)
The postnatal subventricular zone (SVZ) harbors neural stem cells (NSCs) that exhibit robust neurogenesis. However, the epigenetic mechanisms that maintain NSCs and regulate neurogenesis remain unclear. We report that label-retaining SVZ NSCs express Eed, the core component of Polycomb repressive complex 2. In vivo and in vitro conditional knockout and knockdown show Eed is necessary for maintaining NSC proliferation, neurogenesis and neurosphere formation. We discovered that Eed functions to maintain p21 protein levels in NSCs by repressing Gata6 transcription. Both Gata6 overexpression and p21 knockdown reduced neurogenesis, while Gata6 knockdown or p21 overexpression partially rescued neurogenesis after Eed loss. Furthermore, genetic deletion of Eed impaired injury induced SVZ proliferation and emigration. These data reveal a novel epigenetic regulated pathway and suggest an essential role for Eed in SVZ homeostasis and injury.